ANALISIS KEPRIBADIAN TOKOH UTAMA DALAM DUA BELAS NOVEL ANAK KARYA SHERINA SALSABILA - Yuniastuti, Erik; Syam, Christanto; Priyadi, A. Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractResearchers aim to present to the readers want to provide fun, fun entertainment. Literature displays interesting stories, invites the reader to fantasize, bring the reader to a life of power, life that feels attached to it, leads to a game of emotion. The role of literature is not limited by time and space, not limited by age. The second virtue is understanding, understanding formed from the exploration of various life forms, the secrets of life, the discovery and disclosure of various human characters. In short it can be said that this second virtue contains life information. Of course all humans desperately need an information in this life. The study of children's literature is done on 12 novels that have been written by Sherina Salsabila. Twelve children's novels by Sherina Salsabila are chosen on the grounds that the novels have a simple level of understanding, so it is easy to understand the meaning. The language used is easy to understand, the storyline is interesting and not boring. The stories that are presented are stories that are very striking in the lives of children ages 8 s.d. 12 years old.Â Keywords: Structure, Dynamics, Personality Development, Main Leader, Children Literature, Literary LearningÂ